Qur’anic discourse and pragmatic analysis strategies: The Cooperative Principle as a model - brahmia, zina (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract: Most studies about the rhetoric and inimitability of the Qur’an are on one pace. Those studies focused on the composition of the Qur’anic text and the ways of its formulation, in addition to extracting its structural and semantic characteristics. Those studies aimed at uncovering the inimitability of the Qur’an. However, those studies under-investigated the pragmatic dimension that is essential to investigate the Qur’anic discourse. Conversely, the dimension of the purposes of the islamic sharia Maqasid) received wide attention from Al-Shatby and others because it is the basis of extracting Islamic legal rule Pragmatics with its different tools has shed light on different latent aspects of several texts. Hence, We believe that pragmatics and its different concepts will broaden the horizons of Qur'anic studies.